Inovasi Perancangan Sistem Informasi Akuntansi untuk Pelaporan Keuangan UMKM Berbasis SDGs: Kepatuhan SAK EMKM dan Digitalisasi Pelaporan Keuangan - Osesoga, Maria Stefani; Supriyati, Supriyati; Yulianto, Hery Dwi; Bahri, Ramadhan Syaeful; Suherlan, Muhamad Akbar Rahmatullah (Labkat Press KA FTIK UNIKOM, 2024)
The rapid growth of MSMEs does not mean that MSMEs do not have obstacles in carrying out their business activities, especially in managing financial reports which will still be a trend in the coming years to produce sustainable value. Because technology and business have grown together, companies are incentivized to compete by offering the best goods, allowing them to adapt and continue to perform throughout time. So this research aims to develop an innovative financial report accounting information system model for the digitalization transformation of MSMEs. To achieve this goal, the research method is qualitative by collecting data through interviews and observations of MSMEs that have implemented digitalization. As well as collecting data using literature studies to support the study and research framework. The results achieved in this research are an accounting information system model for digitizing MSME financial reports. It is hoped that the resulting model can become a basis for MSMEs to apply digitalization in the preparation of financial reports so that it is expected to produce sustainable value for these MSMEs. Visual business process models seem to be more successful and efficient than textual models in search, recognition, and some inference tasks, and they can accommodate both experts and beginners. Nonetheless, textual models outperform visual models in memory tests (which can be used by professionals and beginners alike) and, to a lesser degree, in problem-solving tasks (which are only used by experts).